Functional metagenomic and metabolomics analysis of gut dysbiosis induced by hyperoxia - Cai, Yulan; Luo, Yanhong; Dai, Ninan; Yang, Yan; He, Ying; Chen, Huajun; Zhao, Manlu; Fu, Xiaoyun; Chen, Tao; Xing, Zhouxiong (Frontiers in Microbiology, 2023)
Background: Inhaled oxygen is the first-line therapeutic approach for maintaining tissue oxygenation in critically ill patients, but usually exposes patients to damaging hyperoxia. Hyperoxia adversely increases the oxygen tension in the gut lumen which harbors the trillions of microorganisms playing an important role in host metabolism and immunity. Nevertheless, the effects of hyperoxia on gut microbiome and metabolome remain unclear, and metagenomic and metabolomics analysis were performed in this mouse study.Methods: C57BL/6 mice were randomly divided into a control (CON) group exposed to room air with fractional inspired oxygen (FiO2) of 21% and a hyperoxia (OXY) group exposed to FiO2 of 80% for 7 days, respectively. Fecal pellets were collected on day 7 and subjected to metagenomic sequencing. Another experiment with the same design was performed to explore the impact of hyperoxia on gut and serum metabolome. Fecal pellets and blood were collected and highperformance liquid chromatography with mass spectrometric analysis was carried out.Results: At the phylum level, hyperoxia increased the ratio of Firmicutes/Bacteroidetes (P=0.049).At the species level, hyperoxia reduced the abundance of Muribaculaceae bacterium Isolate-037 (P=0.007), Isolate-114 (P=0.010), and Isolate-043 (P=0.011) etc. Linear discriminant analysis effect size (LEfSe) revealed that Muribaculaceae and Muribaculaceae bacterium Isolate-037, both belonging to Bacteroidetes, were the marker microbes of the CON group, while Firmicutes was the marker microbes of the OXY group. Metagenomic analysis using Kyoto Encyclopedia of Genes and Genomes (KEGG) and Carbohydrate-Active enZYmes (CAZy) revealed that hyperoxia provoked disturbances in carbohydrate and lipid metabolism. Fecal metabolomics analysis showed hyperoxia reduced 11-dehydro Thromboxane B2-d4 biosynthesis (P=1.10×10 -11 ). Hyperoxia blunted fecal linoleic acid metabolism (P=0.008) and alpha-linolenic acid metabolism (P=0.014). We showed that Gut dysbiosis induced by hyperoxia 3 1-docosanoyl-glycer-3-phosphate (P=1.58×10 -10 ) was the most significant differential serum metabolite inhibited by hyperoxia. In addition, hyperoxia suppressed serum hypoxia-inducible factor-1 (HIF-1, P=0.007) and glucagon signaling pathways (P=0.007).Muribaculaceae with genomic dysfunction of carbohydrate and lipid metabolism. In addition, hyperoxia suppresses unsaturated fatty acid metabolism in the gut and inhibits the HIF-1 and glucagon signaling pathways in the serum.